Effect of F(I)O(2) on physiological responses and cycling performance at moderate altitude - Wilber, R. L.; Holm, P. L.; Morris, D. M.; Dallam, G. M.; Callan, S. D. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: To evaluate physiological responses and exercise performance during a "live high-train low via supplemental oxygen" (LH + TLO(2)) interval workout in trained endurance athletes. METHODS: Subjects (N = 19) were trained male cyclists who were permanent residents of moderate altitude (1800-1900 m). Testing was conducted at 1860 m (P(B) 610-612 Torr, P(I)O(2) approximately 128 Torr). Subjects completed three randomized, single-blind trials in which they performed a standardized interval workout while inspiring a medical-grade gas with F(I)O(2) 0.21 (P(I)O(2) approximately 128 Torr), F(I)O(2) 0.26 (P(I)O(2) approximately 159 Torr), and F(I)O(2) 0.60 (P(I)O(2) approximately 366 Torr). The standardized interval workout consisted of 6 x 100 kJ performed on a dynamically calibrated cycle ergometer at a self-selected workload and pedaling cadence with a work:recovery ratio of 1:1.5. RESULTS: Compared with the control trial (21% O(2)), average total time (min:s) for the 100-kJ work interval was 5% and 8% (P < 0.05) faster in the 26% O(2) and 60% O(2) trials, respectively. Consistent with the improvements in total time were increments in power output (W) equivalent to 5% (26% O(2) trial) and 9% (60% O(2) trial; P < 0.05). Whole-body [VO](2) (L.min-1) was higher by 7% and 14% (P < 0.05) in the 26% O(2) and 60% O(2) trials, respectively, and was highly correlated to the improvement in power output (r = 0.85, P < 0.05). Arterial oxyhemoglobin saturation (S(p)O(2)) was significantly higher by 5% (26% O(2)) and 8% (60% O(2)) in the supplemental oxygen trials. CONCLUSION: We concluded that a typical LH + TLO(2) training session results in significant increases in arterial oxyhemoglobin saturation, [V02] and average power output contributing to a significant improvement in exercise performance.